2017
DOI: 10.1038/nmeth.4143
|View full text |Cite
|
Sign up to set email alerts
|

SMiLE-seq identifies binding motifs of single and dimeric transcription factors

Abstract: Resolving the DNA-binding specificities of transcription factors (TFs) is of critical value for understanding gene regulation. Here, we present a novel, semiautomated protein-DNA interaction characterization technology, selective microfluidics-based ligand enrichment followed by sequencing (SMiLE-seq). SMiLE-seq is neither limited by DNA bait length nor biased toward strong affinity binders; it probes the DNA-binding properties of TFs over a wide affinity range in a fast and cost-effective fashion. We validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(141 citation statements)
references
References 47 publications
5
136
0
Order By: Relevance
“…In an effort to overcome the limitations discussed above, we performed receiver operating characteristic (ROC) curve analyses, an approach that is widely used to evaluate the predictive power of DNA-binding models with respect to in vivo ChIP-seq data (Kulakovskiy et al, 2016; Orenstein and Shamir, 2014; Weirauch et al, 2013; Alipanahi et al, 2015; Mariani et al, 2017; Gordan et al, 2009; Arvey et al, 2012; Isakova et al, 2017). In brief, this approach allowed us to evaluate how well our iMADS models of differential specificity can distinguish between TF1and TF2-preferred ChIP-seq peaks, defined as the top N% and bottom N% of peaks, respectively, sorted according to log ratio of ChIP signals (Figure 5H).…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to overcome the limitations discussed above, we performed receiver operating characteristic (ROC) curve analyses, an approach that is widely used to evaluate the predictive power of DNA-binding models with respect to in vivo ChIP-seq data (Kulakovskiy et al, 2016; Orenstein and Shamir, 2014; Weirauch et al, 2013; Alipanahi et al, 2015; Mariani et al, 2017; Gordan et al, 2009; Arvey et al, 2012; Isakova et al, 2017). In brief, this approach allowed us to evaluate how well our iMADS models of differential specificity can distinguish between TF1and TF2-preferred ChIP-seq peaks, defined as the top N% and bottom N% of peaks, respectively, sorted according to log ratio of ChIP signals (Figure 5H).…”
Section: Resultsmentioning
confidence: 99%
“…Of course, additivity is unlikely to be completely accurate, but there are still only 3 m + 9( m − 1) single variants plus double variants at adjacent positions, where the non-additivity is likely to be most prevalent. But multiple high-throughput methods are now available that provide quantitative binding data from which accurate energy models can be obtained by using appropriate algorithms [16, 1820, 25, 27, 28, 31, 37, 38, 53, 54, 62]. From sufficiently abundant and accurate quantitative binding data one can even skip the modeling and just use the list of relative binding energies to all possible sites (or at least the highest affinity sites that are likely to function as regulatory sites), avoiding approximations entirely (to the degree allowed by the measurement accuracy).…”
Section: Discussionmentioning
confidence: 99%
“…1E). Furthermore, SMILE-seq (12) revealed that ZNF417 and ZNF587 had a higher affinity for methylated than unmethylated versions of this sequence ( fig. S2F).…”
mentioning
confidence: 99%